2017
DOI: 10.1038/srep42258
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Graphene Oxide with Chitosan for Protein Nanocarriers to Protect against Enzymatic Cleavage and Retain Collagenase Activity

Abstract: Proteins have short half-life because of enzymatic cleavage. Here, a new protein nanocarrier made of graphene oxide (GO) + Chitosan (CS) is proposed to successfully prevent proteolysis in protein and simultaneously retain its activity. Bovine serum albumin (BSA) and collagenase were loaded on GO and GO-CS to explore the stability and activity of proteins. SEM, AFM, TEM, DSC, UV-Vis, FT-IR, RBS, Raman, SDS-PAGE and zymography were utilized as characterization techniques. The protecting role of GO and GO-CS agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(82 citation statements)
references
References 85 publications
(114 reference statements)
9
73
0
Order By: Relevance
“…The AuNR showed peaks at 3451, 2868, 1742, 1654, 1460 and 1103 cm −1 corresponding to NH/OH, CH, CO, amide I, amide II, CO groups present in the protein coating of the gold nanorods, respectively . The success of the EDC/NHS conjugation was confirmed firstly by the presence of characteristic amide‐carbonyl (NHCO) stretching (amide I) at 1621 cm −1 in LCGO–AuNR . Second, the disappearance of carboxylic acid stretch (CO) in LCGO–AuNR at 1710 cm −1 indicated that the COOH group of LCGO were consumed in the conjugation to form the amide linkage (Figure b arrow) .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The AuNR showed peaks at 3451, 2868, 1742, 1654, 1460 and 1103 cm −1 corresponding to NH/OH, CH, CO, amide I, amide II, CO groups present in the protein coating of the gold nanorods, respectively . The success of the EDC/NHS conjugation was confirmed firstly by the presence of characteristic amide‐carbonyl (NHCO) stretching (amide I) at 1621 cm −1 in LCGO–AuNR . Second, the disappearance of carboxylic acid stretch (CO) in LCGO–AuNR at 1710 cm −1 indicated that the COOH group of LCGO were consumed in the conjugation to form the amide linkage (Figure b arrow) .…”
Section: Resultsmentioning
confidence: 94%
“…As shown in Figure b, the FTIR spectrum of LCGO presented peaks at 3390, 1710, 1630, 1220, and 1050 cm −1 , which were attributed to the OH bond stretch, CO in carboxylic acid, CC, COC, and CO stretch groups, respectively . The AuNR showed peaks at 3451, 2868, 1742, 1654, 1460 and 1103 cm −1 corresponding to NH/OH, CH, CO, amide I, amide II, CO groups present in the protein coating of the gold nanorods, respectively . The success of the EDC/NHS conjugation was confirmed firstly by the presence of characteristic amide‐carbonyl (NHCO) stretching (amide I) at 1621 cm −1 in LCGO–AuNR .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…ascorbic acid, is quite limited. Several examples reported the added value of using GO and Ch blends: Ch possesses a high number of amine residues that can be exploited for covalent grafting of GO [35][36][37][38][39][40] through amidation reaction with the carboxylic moieties or epoxide ring opening [41]. While amidation requires activation of carboxyls, the epoxide ring opening by primary amines can occur more easily, without activation, but it strongly depends on the amine structure, reaction time, pH and solvent [42]; for example, reaction of GO with polyethyleneimide occurred in water:EtOH 1:1 mixture under reflux for 24 h [43], reaction with TEG diamine occurred in DMF after five days [36], reaction with EDTA occurred in EtOH under sonication for 24 h at room temperature [44].…”
Section: Introductionmentioning
confidence: 99%